2021
DOI: 10.31236/osf.io/yhj9g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective Sports Coaching: A Systematic Integrative Review

Abstract: Research investigating coaching effectiveness is of great importance to ensure the sporting experience and development of athletes is optimised. Coaches are significant figures for the athletes they coach, especially for youth athletes within sporting programmes. Therefore, understanding what makes an ‘effective coach’ in terms of leadership and coaching behaviours will only aid positive youth development and help ensure youth athletes are afforded optimal opportunities to enhance their skills and attributes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Synthesizing the findings from either approaches can help scholars to have a better understanding of the current knowledge, determine the impact of a phenomenon/intervention, identify issues, gaps, and trends, and provide a reference point for future research ( Grant and Booth, 2009 ; Creswell, 2014 ). In the coach leadership area, several scholars have attempted to summarize existing findings employing either systematic literature review ( Gilbert and Trudel, 2004 ; Sheehy et al, 2018 ; Mills and Clements, 2021 ) or meta-analysis ( Kim and Cruz, 2016 ; Kim and Cruz, 2022 ). The findings from the literature review showed that existing studies were mostly focused on the impact of coaches, particularly their behaviors, on athletes’ performance, psychological development, and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesizing the findings from either approaches can help scholars to have a better understanding of the current knowledge, determine the impact of a phenomenon/intervention, identify issues, gaps, and trends, and provide a reference point for future research ( Grant and Booth, 2009 ; Creswell, 2014 ). In the coach leadership area, several scholars have attempted to summarize existing findings employing either systematic literature review ( Gilbert and Trudel, 2004 ; Sheehy et al, 2018 ; Mills and Clements, 2021 ) or meta-analysis ( Kim and Cruz, 2016 ; Kim and Cruz, 2022 ). The findings from the literature review showed that existing studies were mostly focused on the impact of coaches, particularly their behaviors, on athletes’ performance, psychological development, and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the literature review showed that existing studies were mostly focused on the impact of coaches, particularly their behaviors, on athletes’ performance, psychological development, and well-being. It was also found that coach-related studies were aimed to develop, evaluate, or use measurement tools related to examining sources and dimensions of coaching behaviors ( Gilbert and Trudel, 2004 ; Sheehy et al, 2018 ; Mills and Clements, 2021 ). On the other hand, results from the meta-analysis by Kim and Cruz (2016) revealed that coach leadership’s effects on cohesion and athletic satisfaction were moderate and large, respectively, and with gender as a moderating factor for these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that anger expression indirectly predicted performance score through self-efficacy. In line with the current literature on sport coaching, self-efficacy relates to the coaches’ perception of one’s ability to produce desired athletic outcome in athletes and to significantly improved sport performances [ 52 , 53 , 54 ]. Sullivan et al [ 19 ] found that coaches with lower levels of self-efficacy had a decreased perception of athlete skills and a lower level of coaching education compared with coaches who reported higher levels of self-efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is surprising given that communication skills were not among the top-rated standard skills (10.3%), as the existing body of literature related to expertise in coaching gives a lot of attention to communication as a “fuel” to support interpersonal skills, resulting in positive performance-related outcomes ( 53 ), as well as high levels of satisfaction within sports ( 54 ). While it is important to define the key characteristics of successful coaching to ensure competitive athletes' success, the wide range of areas involved in this procedure (e.g., coaching skills, coaching knowledge, and psychological factors) makes it even more challenging to be explored ( 55 ).…”
Section: Discussionmentioning
confidence: 99%